C1q+ Macrophage–Tumor Cell Interaction Promoted Tumorigenesis via GPR17/PI3K/AKT Pathway Induced DNA Hypermethylation in Nasopharyngeal Carcinoma - Yunzhi Liu; Cuicui Huang; Min Luo; Wenfu Lu; Baifeng Zhang; Lu Bai; Shuyue Zheng; Yanan Tan; Shanshan Li; Huali Wang; Lanqi Gong; Xinyuan Guan (Advanced Science, 2025)
Abstract Nasopharyngeal carcinoma (NPC) is one of the common head and neck cancers in Southern China and Southeast Asia. Although current studies have adequately characterized the tumor microenvironment (TME) of NPC, little attention has been paid to how cell‐cell interactions within the TME promote tumorigenesis. In this study, it is found that C1q+ tumor‐associated macrophages (TAMs) are significantly enriched in NPC tumors. Moreover, both enriched C1q+ TAMs and elevated C1q expression are associated with the progression and poor prognosis in NPC patients. In vitro and in vivo studies demonstrate that C1q directly boosts the malignancy and stemness of tumor cells. Mechanistically, C1q activates the Phosphatidylinositol‐3‐kinase (PI3K)/AKT pathway through interacting with GPR17, a member of the G protein‐coupled receptor family, thereby inducing DNA hypermethylation of tumor cells to promote tumor development. It is further proved that DNA hypermethylated NPC cells induced by C1q elicited the immunosuppressive phenotype of TAMs. Targeted blockade of C1q with a neutralizing antibody restricts NPC progression in the humanized mouse model. It is assumed that the differentiation of C1q+ TAMs possibly acquired both M1 and M2 polarization conditions. These findings provide new insights into the cellular communication in the TME of NPC and may have important applications for the development of new targeted therapies.